DETERMINAN KUALITAS AUDIT SATUAN PENGAWASAN INTERN PT. JASA RAHARJA - Akbar, Akbar; Lubis, Bastian; Diana, Fina; Nurmiati, Nurmiati (Universitas Patria Artha, 2024)
This research aims to analyze the influence of integrity, independence, competence and information technology systems on the audit quality of PT Jasa Raharja's internal supervision unit, both partially and simultaneously, as well as the dominant variables that influence it. The population in this study was all 41 PT Jasa Raharja Internal Audit Unit Auditors. Thus, this research is a population or census study, namely 41 respondents. Data analysis in the research used multiple linear regression analysis with the F test and t test. The results of the research show that integrity, independence, competence and information technology systems partially have no effect on the audit quality of the PT Jasa Raharja Internal Audit Unit, while integrity, independence, competence and information technology systems simultaneously influence the audit quality of the PT Jasa Raharja Internal Audit Unit and competency is the most dominant variable influencing the audit quality of the PT Jasa Raharja Internal Audit Unit, so the better an auditor's competency, the better the audit quality of the PT Jasa Raharja Internal Audit Unit.